2009
DOI: 10.1890/08-0105.1
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of genetically engineered crops: fitness effects of virus‐resistance transgenes in wild Cucurbita pepo

Abstract: Abstract. The development of crops genetically engineered for pathogen resistance has raised concerns that crop-to-wild gene flow could release wild or weedy relatives from regulation by the pathogens targeted by the transgenes that confer resistance. Investigation of these risks has also raised questions about the impact of gene flow from conventional crops into wild plant populations. Viruses in natural plant populations can play important roles in plant fecundity and competitive interactions. Here, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 38 publications
4
27
3
Order By: Relevance
“…1 The proportion of susceptible plants infected with zucchini yellow mosaic virus on the two unsprayed (virus-present) fields in which viral diseases were allowed to spread. As with all previous studies of transgenic squash-wild gourd hybrids (Fuchs et al 2004;Laughlin et al 2009;Sasu et al 2009), our study shows that the transgene effectively deters a target virus during introgression from a cultivated to a wild Cucurbita pepo. As has been previously observed in both transgenic squash and transgenic squash-wild gourd hybrids (see Fuchs et al 2004;Sasu et al 2009), a few of the tBC4 plants in this study had mild symptoms of and tested positive for zucchini yellow mosaic virus at the end of the growing season in unsprayed (virus-present) fields in which zucchini yellow mosaic virus was epidemic.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…1 The proportion of susceptible plants infected with zucchini yellow mosaic virus on the two unsprayed (virus-present) fields in which viral diseases were allowed to spread. As with all previous studies of transgenic squash-wild gourd hybrids (Fuchs et al 2004;Laughlin et al 2009;Sasu et al 2009), our study shows that the transgene effectively deters a target virus during introgression from a cultivated to a wild Cucurbita pepo. As has been previously observed in both transgenic squash and transgenic squash-wild gourd hybrids (see Fuchs et al 2004;Sasu et al 2009), a few of the tBC4 plants in this study had mild symptoms of and tested positive for zucchini yellow mosaic virus at the end of the growing season in unsprayed (virus-present) fields in which zucchini yellow mosaic virus was epidemic.…”
Section: Discussionsupporting
confidence: 91%
“…In our virus-present fields, the reproductive output of the ntBC4 plants was only 61% of that of the tBC4 plants. The fitness advantage of the transgenic plants in this study, however, was not as great as that observed in the Fuchs et al (2004) and Laughlin et al (2009) studies. For example, Laughlin et al (2009) hand-inoculated all of the susceptible plants as seedlings with zucchini yellow mosaic virus and removed all wilt-diseased plants from their fields and their analyses, and they found that the susceptible plants produced only 6% of the fruits and 3% of the seeds of the transgenic introgressives in the same fields.…”
Section: Effects Of the Transgene On Fitnesscontrasting
confidence: 91%
See 2 more Smart Citations
“…Despite its ability to unambiguously identify resistance costs , the NILs protocol has rarely been used (pathogen resistance: Heidel et al, 2004;Korves and Bergelson, 2004;Laughlin et al, 2009;herbicide resistance: McCloskey andHolt, 1990, 1991;Salzmann et al, 2008;Wang et al, 2010) (Table 1; Supplementary Table S1). Several plant generations are required to produce NILs in order to disrupt linkage disequilibrium between resistance and other genes.…”
Section: Eliminating the Effects Of Genetic Background On Costsmentioning
confidence: 99%